Malnutrition is associated with increased disease risk in older people in the Makkah region of Saudi Arabia: A cross-sectional study - Althaiban, Maha A.; Aljefree, Najlaa M.; Almoraie, Noha M.; Shatwan, Israa M. (Frontiers in Public Health, 2023)
Introduction There is little research on the nutritional status of older people in Saudi Arabia. This study investigated the factors associated with the nutritional status of older people in the Makkah region, Saudi Arabia. We hypothesized that older people who are at risk of malnutrition are at higher risk of different diseases. Materials and methods This cross-sectional study surveyed 271 people aged ≥60 years from October 2021 to January 2022. We collected data on demographics, body mass index, the Geriatric Depression Scale-Short Form, Geriatric Oral Health Assessment Index, Mini Nutritional Assessment, Eating Attitudes Test, and Household Dietary Diversity score. Results Among the 271 participants, 13.3% were malnourished and 53.9% were at risk of malnutrition. The oral health (P < 0.001), depression (P < 0.001), and eating disorder (P < 0.002) scores were significantly associated with malnutrition. Congestive heart failure, asthma, peripheral vascular disease, Alzheimer's disease, and hypertension were more prevalent among malnourished participants—this supports our original hypothesis. The HDD score showed no significant differences between men and women. Conclusion Malnutrition was associated with overweight or obesity, poor oral health, and depression. Older people in the Makkah region, Saudi Arabia, had a high risk of malnutrition.